PENGEMBANGAN TES KREATIVITAS - Avianti, Ratu Amilia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2015)
This research aims to develop creativity test. This research was conducted in Jakarta. Validity and relaibility test were designed with three calibration phases: (1) expert assessment phase, (2) empirical test phase Phase I, and (3) an empirical test phase II. Samples were selected based on purposive cluster random sampling. Factor analysis of empirical test involving 200 students in the sample, showed that the dimensions developed by the results of the factor analysis in accordance with the theoretical. The results showed that the test alliteration reading creativity consists of five dimensions, namely (1) the smoothness of thinking, (2) flexibility of thinking, (3) originality of ideas, (4) the new arrangement, and (5) of detail. Five dimensions are translated into 18 grains of questions or statements as a stimulus in generating creative ideas. Results of factor analysis showed that each factor has a load factor greater than 0.3. Results of factor analysis showed that the creativity test contains 4 items figural tests and 12 tests verbal. Creativity tests developed have Î± reliability coefficient of 0.822. ÆŸ amounted to 0.866, and Î© is 0.944.